2012
DOI: 10.1371/journal.pone.0035751
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Treatment to Old Alzheimer's Mice Reverses β-Amyloid Deposition, Modifies Cerebral Blood Flow, and Provides Selected Cognitive Benefit

Abstract: Few studies have investigated physiologic and cognitive effects of “long-term" electromagnetic field (EMF) exposure in humans or animals. Our recent studies have provided initial insight into the long-term impact of adulthood EMF exposure (GSM, pulsed/modulated, 918 MHz, 0.25–1.05 W/kg) by showing 6+ months of daily EMF treatment protects against or reverses cognitive impairment in Alzheimer's transgenic (Tg) mice, while even having cognitive benefit to normal mice. Mechanistically, EMF-induced cognitive benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
77
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 51 publications
6
77
0
Order By: Relevance
“…These previous studies suggested that long‐term RF‐EMF exposure might be required to improve cognitive performance in AD mice, although some previous studies also showed a beneficial memory effect following exposure for periods shorter than 3 months. For example, in old (21–27 months old) APPsw AD model mice, 2 months of RF‐EMF exposure seemed to produce a cognitive benefit, as demonstrated by Y‐maze and radial arm water maze performance [Arendash et al, 2012]. In the triple transgenic mouse model of AD (3xTg‐AD), exposure to 2.4 GHz EMF signals for 28 days resulted in memory enhancement when mice were assessed via cognitive interference and Barnes maze test [Banaceur et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous studies suggested that long‐term RF‐EMF exposure might be required to improve cognitive performance in AD mice, although some previous studies also showed a beneficial memory effect following exposure for periods shorter than 3 months. For example, in old (21–27 months old) APPsw AD model mice, 2 months of RF‐EMF exposure seemed to produce a cognitive benefit, as demonstrated by Y‐maze and radial arm water maze performance [Arendash et al, 2012]. In the triple transgenic mouse model of AD (3xTg‐AD), exposure to 2.4 GHz EMF signals for 28 days resulted in memory enhancement when mice were assessed via cognitive interference and Barnes maze test [Banaceur et al, 2013].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no effect of RF‐EMF exposure on spatial learning and working memory tasks was found [Sienkiewicz et al, 2000; Dubreuil et al, 2003; Maaroufi et al, 2014]. Moreover, other studies have reported a beneficial effect of RF‐EMF on cognitive function [Dragicevic et al, 2011; Arendash et al, 2012; Banaceur et al, 2013]. Thus, there is some controversy regarding the effects of RF‐EMF on cognitive functions and associated hippocampal functions, and further mechanistic investigations and time‐point analyses are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Although recent evidence would suggest otherwise, [61,62] it has been demonstrated that chronic pulse application of RF can revert both deposition of β amyloid and ameliorate cognitive deficit in mice [63]. A similar effect was also obtained in either wild type and mutated mice [64], where RF exposure increased mitochondrial activity and reduced cerebral blood fluid and seemed to facilitate soluble β amyloid removal from the CNS district. Interestingly, Banaceur and co-workers [65] pointed their attention to another aspect not yet fully investigated namely Wi-Fi radiofrequencies (2.40 GHz SAR 1.6 W/kg).…”
Section: The Effect Of Rf Exposure In Vivo: New Insights On Biosystemmentioning
confidence: 95%
“…By contrast, neurobiological evidence that might support a therapeutic application of TMS to AD is lacking. It is reported that exposure to very weak high-frequency electromagnetic field (918 MHz), such as the one emitted from a cellular phone to the phone caller, improves cognitive deficits and reduced Ab burden in AD model mice (Arendash et al, 2012), though this procedure and TMS are different. TMS is shown to induce or modulate synaptic plasticity in normal rodents or rabbits (Wang et al, 1996;Levkovitz et al, 1999;Ogiue-Ikeda et al, 2003) and in aging rats as well (Levkovitz and Segal, 2001), but not yet in AD model animals.…”
Section: Introductionmentioning
confidence: 99%